Posaconazole MIC distributions for Aspergillus fumigatus SC by four methods: Impact of Cyp51A mutations on estimation of epidemiological cutoff values - Espinel-Ingroff, A. (2018)
Estimating epidemiological cutoff endpoints (ECVs/ECOFFS) may be hindered when there is overlap between MICs for strains that are genetically wild type (WT) and non-WT (harboring cyp51A mutations). We collected posaconazole MIC distributions for Aspergillus fumigatus SC from 26 laboratories (Australia, Canada, Europe, India, South/North America and Taiwan), and published studies. Distributions that fulfilled CLSI criteria were pooled and ECVs were estimated. The sensitivity of two ECV calculation analytical techniques was examined, ECOFFinder and NRI, to the inclusion of non-WT MICs in each WT distribution to be analyzed. The total MICs by the CLSI, EUCAST, Etest, and SYO methods were respectively: 2,223 WT & 274 non-WT; 556 WT & 52 non-WT; 1,365 WT & 29 non-WT, and 381 non-WT. A significant overlap in posaconazole MICs between WT A. fumigatus and those harboring cyp51A mutations was observed. At the most commonly chosen percentage of the modelled wild type population (97.5 %), almost all ECVs remained the same when the MICs for non-WT isolates were merged with the WT distribution: ECOFFinder ECVs 0.5 μg/ml (CLSI) and 0.25 μg/ml (EUCAST and Etest); all NRI ECVs: 0.5 μg/ml. However, the 95 % ECOFFinder CLSI ECV for the WT distribution was 0.25 μg/ml (a more clinically relevant endpoint) versus 0.5 μg/ml when non-WT values were merged. The tentative SYO ECOFFinder was 0.06 μg/ml (3/8 laboratories data). It appears that ECV definition techniques are not vulnerable to overlap between genetically WT and non-WT when up to 11.6 % of the MIC distribution includes non-WT.